ANALISIS KETRAMPILAN BERPIKIR KRITIS DALAM PEMBELAJARAN TEMATIK BERBASIS MASALAHANALISIS KETRAMPILAN BERPIKIR KRITIS DALAM PEMBELAJARAN TEMATIK BERBASIS MASALAH - Nur Asiah; Harjoni Desky (CV Putra Publisher, 2022)
This study aims to identify critical thinking skills for problem-based approaches in thematic education. The research subjects were fourth-grade elementary school students in an even semester with 23 students. Method of gathering information using observation. The research instrument uses an observation sheet. The information analysis method is a comparative descriptive method. The research results reported an increase in the critical thinking skills of fourth-grade students in thematic education using a problem-based approach. The average increase in the critical thinking of the scale participants in cycles one and two increased by 3.87%. The average critical thinking of students in cycle one was initially at 68.86%. After that, it grew to 70.73% in cycle two. Increasing the critical thinking skills of fourth-grade students in thematic education through a problem-based approach with the steps: 1) Orienting students to problems, 2) Organizing into groups for student learning, 3) Guiding individual and group investigations, 4) Developing and presenting results, 5) Analyze and evaluate the problem-solving process.